Policy implementation the transition period: A case study at Tangerang - Raharusun, Felix; Wasistiono, Sadu; Simangunsong, Fernandes; Pitono, Andi (International Journal Labs, 2023)
The total assets managed by the UPK in Tangerang Regency are IDR 47,424,689,719, if the UPK does not transform into a Joint BUMD there is a chance that the government will lose these funds, because the management of the UPK is managed privately. The aim of this research is to implement policies, determinant factors that determine policy implementation, and strategies for optimizing the policy transition of establishing managers of ex-PNPM-MP community revolving fund activities into joint village-owned enterprises in Tangerang Regency, Banten Province. This research uses the policy implementation theory proposed by Hamdi. The research method used is a qualitative approach with descriptive research type. The data analysis technique used is data reduction and drawing conclusions. The research results show that the implementation of the transition policy for the formation of Ex-PNPM-MP Community Revolving Fund Activity Managers to become BUMDesma has not been optimal. This is proven by the research results that there is no former PNPM-MP DBM Activity Management Unit that has implemented the transformation process. Policy Transition: 1) Unfreezing Stage, namely socialization and communication steps as well as organizational/institutional strengthening. 2) The Movement Stage, namely the step of sharing understanding about the transformation process. 3) Refreezing stage, namely the leadership role and connections between programs. Policy implementation strategies during the transition period: communication and socialization and institutions.